The Hammock as a Therapeutic Alternative at The Neonatal Intensive Care Unit - Pereira, Silvana Alves; Filho, Gentil Gomes da Fonseca; Holanda, Norrara Scarlytt de Oliveira; Vieira, Daniela Elizabeth de Castro; Moran, Cristiane Aparecida (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Among the therapeutic alternatives complementary to humanized care, there is the vestibular stimulation. Provided by the gentle swing in a hammock, it simulates the containment and maternal movements found in the intrauterine environment and is considered a safe method that reduces stress levels in very low birthweight premature newborn (PTNB). Objective: To observe the time of hospitalization and the discharge weight of the PTNB that passed through the positioning in the hammock and kangaroo mother care. Methods: A quasi-experimental study involving two university hospitals including PTNB. The PTNB were allocated into two groups: Kangaroo Mother Care (KMC) composed by PTNB selected according to the maternal presence and vestibular stimulation (VS) composed by PTNB whose maternal presence was not possible. The KMC were kept in skin-to-skin contact with the mother. The VS were positioned in dorsal decubitus in a hammock of cotton adapted within the incubator. The time of hospitalization and weight monitoring were recorded daily by the nursing team in a collection form. Results: From the 40 PTNB included in this study, 47.5% were female and 40% had normal birth, 20 of them were allocated in the VS group and 20 in the KMC group. The time of hospitalization were not different between the groups (p=0.12), but the discharge weight were higher in the VS group (p<0.05). Conclusion: The data indicate that the hospitalization time is similar between the PTNB who received KMC and VS, and that the discharge weight is higher for the group that received the VS.